Mobilizing social capital: Which informal and formal supports affect employment outcomes for HOPE VI residents?. Issue 7 (2nd October 2016) - Nguyen, Mai Thi; Rohe, William; Frescoln, Kirstin; Webb, Michael; Donegan, Mary; Han, Hye-Sung
Abstract: Using a mixed-methods approach, this study examines the relationship between informal social support and formal support services and employment outcomes among residents of a public housing development relocated as part of a HOPE VI project in Charlotte, North Carolina. Informal social supports are resources accessible through family and friends within a neighborhood and formal support services are provided by case managers and service providers. We find that when former public housing residents are enrolled in case management longer and have high satisfaction with their case manager, this leads to better employment outcomes. In addition, having strong bonding ties among public housing neighbors has a negative influence on employment. This study sheds light on how case managers play a role in promoting economic mobility by mitigating social and economic crises and providing bridging capital for poor families.